2016
DOI: 10.1038/nm.4037
|View full text |Cite
|
Sign up to set email alerts
|

Rescue of GABAB and GIRK function in the lateral habenula by protein phosphatase 2A inhibition ameliorates depression-like phenotypes in mice

Abstract: The lateral habenula (LHb) encodes aversive signals, and its aberrant activity contributes to depression-like symptoms. However, a limited understanding of the cellular mechanisms underlying LHb hyperactivity has precluded the development of pharmacological strategies to ameliorate depression-like phenotypes. Here we report that an aversive experience in mice, such as foot-shock exposure (FsE), induces LHb neuronal hyperactivity and depression-like symptoms. This occurs along with increased protein phosphatase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
148
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 149 publications
(159 citation statements)
references
References 56 publications
8
148
3
Order By: Relevance
“…Pharmacological inhibition of LHb by the GABA agonist muscimol had antidepressant effects in congenital helpless rats (33), and opposite metabolic alterations in Hb (high) and VTA (low) were observed in these rats (34). A very recent study also showed that enhancement of GABA-GIRK function in the LHb ameliorates depressive-like behaviors in mice (35). …”
Section: Depressionmentioning
confidence: 97%
“…Pharmacological inhibition of LHb by the GABA agonist muscimol had antidepressant effects in congenital helpless rats (33), and opposite metabolic alterations in Hb (high) and VTA (low) were observed in these rats (34). A very recent study also showed that enhancement of GABA-GIRK function in the LHb ameliorates depressive-like behaviors in mice (35). …”
Section: Depressionmentioning
confidence: 97%
“…Recently, an aversive stimulus, i.e., inescapable foot shock, was shown to decrease GABA B R-GIRK currents in LHb neurons [95]. Though the stimulus was different, the plasticity in GABA B R-GIRK currents may depend on the same PP2A-mediated GABA B2 S783 dephosphorylation mechanism described in VTA GABA neurons with psychostimulants [90, 95]. To confirm this, additional experiments are needed to determine whether there is a change in phosphorylation of GABA B2 S783.…”
Section: Mechanisms Of Girk Channel Regulation In Health and Addictionmentioning
confidence: 99%
“…To confirm this, additional experiments are needed to determine whether there is a change in phosphorylation of GABA B2 S783. Significantly, systemic administration of a PP2A inhibitor, LB-100, ameliorated the depressive-like behavioral effects of inescapable foot shock [95]. …”
Section: Mechanisms Of Girk Channel Regulation In Health and Addictionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, in rodent models of addiction and depression, glutamatergic and GABAergic synaptic plasticity modulates LHb neuronal firing, which is in turn instrumental for depression-like phenotypes (Lecca et al., 2016, Maroteaux and Mameli, 2012, Meye et al., 2015, Shabel et al., 2014). This highlights the behavioral relevance of synaptic adaptations in the LHb, heightening the need of understanding its underlying cellular processes.…”
Section: Introductionmentioning
confidence: 99%